2015
DOI: 10.5489/cuaj.2414
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient percutaneous nephrolithotomy in a renal transplant patient: World’s first case

Abstract: Percutaneous nephrolithotomy (PCNL) is an established safe and effective surgical treatment option for renal calculi in renal allografts. The advent of tubeless PCNL has led to reports of ambulatory or outpatient PCNL. This case report describes the successful outpatient management of a 49-year-old female with a symptomatic renal pelvic calculus in her transplanted kidney. Tubeless PCNL successfully removed the stone, free of complication, and the patient was discharged 2 hours and 17 minutes after the procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…9 Transplant recipients are more predisposed to developing urolithiasis due to their conditions such as: hyperfiltration, excessively alkaline urine, renal tubular acidosis, obstructive uropathy, recurrent urinary tract infections, and increased serum calcium caused by persistent tertiary hyperparathyroidism. [10][11][12][13][14] Many series have reported the mean time of posttransplantation lithiasis between 1.6 to 3.6 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Transplant recipients are more predisposed to developing urolithiasis due to their conditions such as: hyperfiltration, excessively alkaline urine, renal tubular acidosis, obstructive uropathy, recurrent urinary tract infections, and increased serum calcium caused by persistent tertiary hyperparathyroidism. [10][11][12][13][14] Many series have reported the mean time of posttransplantation lithiasis between 1.6 to 3.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 And also, the proximity to the bony pelvis causes that targeting the shock wave directly onto the stone becomes more difficult in ESWL. 1,4,9,10,22 But the anatomic position in the iliac fossa with the renal surface close to skin makes PCNL an attractive alternative and a feasible procedure in the treatment of urinary calculi. 10 Many cases have been reported in which allograft lithiass was treated successfully with PCNL.…”
Section: 391121mentioning
confidence: 99%
See 2 more Smart Citations
“…With experience, its application can even be extended to patients with more complex stone disease and higher BMI. Its use has also been described for bilateral simultaneous PCNL cases and in a renal transplant patient [10,17]. Crook et al [18] previously reported the length of stay to be significantly reduced when patients undergo TT technique compared with those receiving PNT placement (2.3 vs 3.4 d, p < 0.05).…”
Section: Advantages Of Ambulatory Pcnlmentioning
confidence: 99%